53 interesting things to do in your lectures - Gibbs, Graham (Bristol : Technical and Educational Services, 1988)
This is a practical how-to book for teaching staff in higher and professional education. The topics covered are wide-ranging. They include: structuring the lecturing process; improving students' notes; structuring and summarising content; linking lectures to each other; holding the students' attention; promoting active learning during lectures
Preface; Glossary. Ch. 1: Structuring the process Ch. 2: Improving students notes Ch. 3: Using handouts Ch. 4: Structuring and summarising content Ch. 5: Linking lectures Ch. 6: Holding Attention Ch. 7: Active attention during lectures Ch. 8: Checking on learning
Keywords: teaching aptitude -- reference book; teaching technique